2003
DOI: 10.1081/cnv-120022359
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Modified deGramont 5-Fluorouracil, Leucovorin, and Oxaliplatin in Previously Treated Patients with Metastatic Colorectal Cancer

Abstract: The modified deGramont regimen of 5-FU, leucovorin, and oxaliplatin is tolerable and is associated with a modest degree of antitumor activity in patients who have progressed on both 5-FU and irinotecan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Median survivals were higher than 20 months in both arms. Yet, when administered in second-line treatment, both FOLFOX and FOLFIRI had limited efficacy, which was consistent with the results of the Ryan's Phase II study assessing FOLFOX-4 in irinotecanpretreated patients (17). Furthermore, an important limitation was a frequent Grade 3 sensory-neuropathy, which occured in 34 percent of the patients initially treated by FOLFOX (10).…”
Section: Discussionsupporting
confidence: 57%
“…Median survivals were higher than 20 months in both arms. Yet, when administered in second-line treatment, both FOLFOX and FOLFIRI had limited efficacy, which was consistent with the results of the Ryan's Phase II study assessing FOLFOX-4 in irinotecanpretreated patients (17). Furthermore, an important limitation was a frequent Grade 3 sensory-neuropathy, which occured in 34 percent of the patients initially treated by FOLFOX (10).…”
Section: Discussionsupporting
confidence: 57%
“…Moertel demonstrated a 40% reduction in the disease recurrence rate (P = 0.0001) and a 33% reduction in the mortality for stage III patients (P = 0.0007) using fluorouracil and levamisole. 5 The National Surgical Adjuvant Breast and Bowel Project (NSABP 21 ), the North Central Cancer Treatment Group (NCCTG 2 ), and the International Multicentre Pooled Analysis of Colon Cancer Trials (IMPACT 3 ) also reported a significant survival benefit of adjuvant chemotherapy using fluorouracil and leucovorin (FU/LV [22][23][24][25][26][27]. FU/LV is considered the standard regimen for adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 97%